2019
DOI: 10.1088/1748-9326/ab051e
|View full text |Cite
|
Sign up to set email alerts
|

Effective moratoria on land acquisitions reduce tropical deforestation: evidence from Indonesia

Abstract: The tropics have suffered substantial forest loss, and elevated deforestation rates have been closely linked to large-scale land acquisitions (LSLA). Having a timely and accurate understanding of global LSLA pattern will be critically important for concluding related policies and actions. Here, we investigate global LSLA networks and find that land acquisitions are characterized by dominant acquisition flows from the developing to the developed world (75.4%), and less of these flows are retained within the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…We have shown that the impact of these fluxes on the atmospheric carbon pool can be larger than emission factors for soil carbon loss alone might suggest, and that is highly unlikely that ‘carbon debts’ incurred early in a plantation lifecycle could be recouped over the remaining years. Evidence has shown that moratoria on peatland conversion within protected areas can be effective (Chen et al, 2019) but huge challenges remain, and newly identified areas of extensive peatland being reported from tropical zones across the globe (Lähteenoja & Page, 2011; Xu et al, 2018) reveal regions that may be particularly vulnerable to land‐use change. Despite policy development in South East Asia, limitations in regulatory frameworks and enforcement capabilities combined with political and socio‐economic factors still challenge peatland protection (Padfield et al, 2016; Wijedasa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the impact of these fluxes on the atmospheric carbon pool can be larger than emission factors for soil carbon loss alone might suggest, and that is highly unlikely that ‘carbon debts’ incurred early in a plantation lifecycle could be recouped over the remaining years. Evidence has shown that moratoria on peatland conversion within protected areas can be effective (Chen et al, 2019) but huge challenges remain, and newly identified areas of extensive peatland being reported from tropical zones across the globe (Lähteenoja & Page, 2011; Xu et al, 2018) reveal regions that may be particularly vulnerable to land‐use change. Despite policy development in South East Asia, limitations in regulatory frameworks and enforcement capabilities combined with political and socio‐economic factors still challenge peatland protection (Padfield et al, 2016; Wijedasa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of the transition to large-scale oil palm agriculture remain locally contested, as they have been accompanied by large losses in natural landscapes, negative ecological outcomes, and reductions in biodiversity services (Austin et al, 2019(Austin et al, , 2017Clough et al, 2016;Denmead et al, 2017). Licensing oil palm production has been shown to double deforestation rates (Busch et al, 2015;Chen et al, 2019). In addition to the environmental externalities, the expansion of the palm oil industry has been related to land consolidation, conflict over traditional land rights, and water scarcity (Colchester et al, 2007;Rist et al, 2010;Abram et al, 2017;Merten et al, 2016).…”
Section: The Palm Oil Boommentioning
confidence: 99%
“…(Sguazzin & Mbatha, 2019). In Indonesia, there is a continuing moratorium on new timber leases (Chen et al, 2019). In Cambodia, allegations persist that the country's ruling elite, including its government and military, has perpetuated human rights violations by grabbing land and forcibly evicting an estimated 350,000 people over the past two decades (Vidal & Bowcott, 2016).…”
Section: The Global Picture: Land Acquisition or Criminal Land Grab?mentioning
confidence: 99%